Tribe and State in Asia through Twenty-Five Centuries. - Guha, Sumit (Asia shorts., 2021)
This book analyzes how the word "tribe" has morphed and spread through the centuries. It goes behind the label to bring out the social, military, and environmental settings that gave it its various meanings.